(untitled) (Research, Society and Development, 2022)
Introduction: Columnar epithelium in the distal esophagus and biopsies with intestinal metaplasia define Barrett’s esophagus (EB). The objective was to identify the association of EB and esophageal mucosa lesions in histopathological reports. Methods: a retrospective and cross-sectional study with 1953 reports of esophageal mucosa. Results: 1953 biopsies of esophageal mucosa lesions were analyzed. We identified 133 (6.8%) of Barrett’s esophagus, 151 (7.7%) with H.pylori and of these, 17 (11.3%) (p =0.041) were associated with Barrett’s esophagus. The mean age group was 52 years old (IQR 42.5-62.5), male prevalence (63.2%). Lesions associated with EB: metaplasia 23 (17.3%) (p=0.004); dysplasia 8 (6%) (p<0.001), and 8 (100%) had low-grade dysplasia (p<0.001) and esophagitis with 34 (25.6%) reports, 33 (97%) of the chronic type . No association with malignancy was identified. As for the gross and adjusted relative risks, the following were significant: age (RR: 1.03 (95%CI: 1.02-1.04)) and RRa (95%CI) 1.03 (1.02-1.03), male sex, RR (95%CI) 1.76 (1.25-2.48) and RRa (95%CI) 1.03 (1.02-1.03) and dysplasia. Esophagitis, metaplasia and eosinophilic esophagitis were not likely to be at risk. There was a high probability of carcinogenic exposure regarding dysplasia (p=0.002) RR 5.83 (3.29-10.32), RRa 2.63 (1.45-4.78). Esophagitis was diagnosed in 1,416 reports of the total sample. When correlating with metaplasia, it was statistically significant (RR: 1.27; 95%CI: 1.14-1.42). Conclusion: male patients over 50 years of age with dysplasia and absence of esophagitis had a higher risk of Barrett’s esophagus. Those who had metaplasia and eosinophils >=15 eos/AGC without lesions glycogenic acanthosis and polyps were at risk for esophagitis. The presence of metaplasia alone did not represent a risk factor for EB, although esophagitis seems to represent a greater risk for the development of metaplasia. Low-grade dysplasia was associated with a high carcinogenic probability.